2009
DOI: 10.1001/jama.2009.976
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Levels and Risk of Type 2 Diabetes

Abstract: ContextThe association of obesity with development of type 2 diabetes may be partly mediated by altered secretion of adipokines by adipose tissue. Greater adiposity downregulates secretion of adiponectin, an adipokine with anti-inflammatory and insulinsensitizing properties. The strength and consistency of the relation between plasma adiponectin and risk of type 2 diabetes is unclear.Objective To systematically review prospective studies of the association of plasma adiponectin levels and risk of type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
520
3
14

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 901 publications
(569 citation statements)
references
References 42 publications
(119 reference statements)
32
520
3
14
Order By: Relevance
“…Consistent with this, analysis of plasma adiponectin complexes in CML patients, before and after 3 months of imatinib therapy, revealed a significant increase in the level of HMW complexes . In humans, adiponectin levels correlate negatively with insulin resistance and metabolic syndrome, with low adiponectin levels being associated with a higher risk of type 2 diabetes (Li et al 2009). Thiazolidinedione compounds, a class of anti-diabetic drugs that improve systemic insulin sensitivity, are thought to work, at least in part, by promoting the formation of small adipocytes that secrete high levels of HMW adiponectin , Phillips et al 2003, Nawrocki et al 2006.…”
Section: Imatinib Promotes Adipogenesis S Fitter and Others 235mentioning
confidence: 99%
“…Consistent with this, analysis of plasma adiponectin complexes in CML patients, before and after 3 months of imatinib therapy, revealed a significant increase in the level of HMW complexes . In humans, adiponectin levels correlate negatively with insulin resistance and metabolic syndrome, with low adiponectin levels being associated with a higher risk of type 2 diabetes (Li et al 2009). Thiazolidinedione compounds, a class of anti-diabetic drugs that improve systemic insulin sensitivity, are thought to work, at least in part, by promoting the formation of small adipocytes that secrete high levels of HMW adiponectin , Phillips et al 2003, Nawrocki et al 2006.…”
Section: Imatinib Promotes Adipogenesis S Fitter and Others 235mentioning
confidence: 99%
“…Risk of T2DM appeared to decrease with increasing adiponectin levels. Currently, adiponectin is one of the strongest biochemical predictors of T2DM [116]. In this study, diabetic patients showed significantly decreased serum adiponectin levels compared to the controls.…”
Section: Resultsmentioning
confidence: 50%
“…Adiponectin affects the gluconeogenesis process and fatty acid oxidation through 5' adenosine monophosphate-activated protein kinase (AMP)-dependent protein kinase and peroxisome proliferator-activated receptor (PPAR) in the liver. Moreover, it increases glucose uptake in the peripheral tissues and stimulates insulin secretion, ultimately leading to a regulation of the body's energy (25). The interaction between adiponectin and adapter proteins, such as adaptor protein containing PH domain, phosphotyrosinebinding domain, and leucine zipper, is important in the adiponectin signaling pathway and for an increase in insulin sensitivity (26).…”
Section: Effect On Adiponectin Releasingmentioning
confidence: 99%